2004
DOI: 10.1161/01.cir.0000136825.96029.a5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti–Heat Shock Protein 65 Antibodies With Development of Postoperative Atrial Fibrillation

Abstract: Background-Atrial fibrillation (AF) is a frequently encountered arrhythmia after cardiac surgery, but its underlying mechanisms are still unclear. We hypothesize that autoimmune and inflammatory responses against heat shock protein 65 (HSP65) may be involved and hence examined the relationship between HSP65 autoantibodies and occurrence of postoperative AF. Methods and Results-A prospective study of 329 patients undergoing elective primary CABG was undertaken.Cardiovascular risk factors, ECG characteristics, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The median age was 65 years (40–80 years). Exclusion criteria were preceding history of AF, other associated operations, acute coronary event within 6 weeks before surgery, active infection, history of autoimmune diseases, and use of immunosuppressive drugs [27]. Demographic data, cardiovascular risk factors, and usage of medications, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The median age was 65 years (40–80 years). Exclusion criteria were preceding history of AF, other associated operations, acute coronary event within 6 weeks before surgery, active infection, history of autoimmune diseases, and use of immunosuppressive drugs [27]. Demographic data, cardiovascular risk factors, and usage of medications, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…13 Maixent and colleagues 15 speculated on the possibility of an autoimmune process after finding circulating antimyosin autoantibodies in the serum of patients who had lone AF. Mandal and associates 17 investigated the effects of heat-shock proteins (HSPs), a group of chaperone proteins that preserve cellular integrity by keeping proteins in their correctly folded state. Their study showed that the inflammationinduced expression of HSPs on the surface of myocytes might lead to cell lysis by circulating anti-HSP65 antibodies, with subsequent structural myocardial changes leading to AF after cardiac surgery.…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 99%
“…1 We agree that ␤-blocker use has been associated with postoperative AF in many of the previous trials and studies. From the point of view of associated pathophysiology, it is acute withdrawal of ␤-blockers in the postoperative period that makes these patients more prone to postoperative AF.…”
Section: Responsementioning
confidence: 55%